Morphophysiological Responses of the Goat Mammary Gland to Water Scarcity in Arid and Semi-Arid Environments: Are They Enough to Generate Adaptation to New Climatic Challenges? - Carolina Geldsetzer-Mendoza; José Luis Riveros (Animals, 2023)
Due to climate change, diverse territories of the planet will suffer from water restrictions. Goats are perceived as the most resilient ruminants in this scenario. So, various studies have focused on describing how a lower water intake influences milk production, especially in breeds adapted to desert environments. In water-stress situations, goats lose up to 32% of their body weight (BW), the rate of passage is reduced, and the digestibility of the feed increases. When goats consume water again, the rumen prevents hemolysis and osmotic shock from occurring. Regarding milk production, the response varies depending on the breed and the level of water restriction, maintaining the milk volume or reducing it by up to 41%. Systemically, it decreases the urinary volume and glomerular filtration rate, increasing blood osmolality and the vasopressin (ADH) concentration. Studies are scarce regarding changes in blood flow to the mammary gland, but there would be a reduction in blood flow velocity of up to 40% without changing blood pressure. New studies must be undertaken to determine which breeds or crosses are the best adapted to changing environmental conditions and to improve our understanding of the changes that occur at the morphophysiological level of the caprine mammary gland.